2010
DOI: 10.1038/aps.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of prostaglandin E1 on human umbilical vein endothelial cell injury induced by hydrogen peroxide

Abstract: Aim: To investigate the protective effects of prostaglandin E 1 (PGE 1 ) against H 2 O 2 -induced oxidative damage on human umbilical vein endothelial cells (HUVECs). Methods: HUVECs were pretreated with PGE 1 (0.25, 0.50, and 1.00 µmol/L) for 24 h and exposed to H 2 O 2 (200 µmol/L) for 12 h, and cell viability was measured by the MTT assay. LDH, NO, SOD, GSH-Px, MDA, ROS, and apoptotic percentage were determined. eNOS expression was measured by Western blotting and real-time PCR. Results: PGE 1 (0.25−1.00 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
0
26
0
1
Order By: Relevance
“…The number of blue-stained dead cells and non-stained living cells were then counted with a hemacytometer within 3 min. The cell mortality rate (%) was calculated as the number of dead cells divided by the number of total cells, multiplied by 100 (Fang et al 2010;Valadares et al 2009;Wang et al 2009a, b).…”
Section: Flow Cytometric Detection Of Apoptotic Cellsmentioning
confidence: 99%
“…The number of blue-stained dead cells and non-stained living cells were then counted with a hemacytometer within 3 min. The cell mortality rate (%) was calculated as the number of dead cells divided by the number of total cells, multiplied by 100 (Fang et al 2010;Valadares et al 2009;Wang et al 2009a, b).…”
Section: Flow Cytometric Detection Of Apoptotic Cellsmentioning
confidence: 99%
“…Prostaglandin E1 (Alprostadil ® , PGE1), which is an important member of the prostaglandin (PG) family, is a product of arachidonic acid metabolism by cyclooxygenase [66,67]. Similar to NO, PGE1 has cardioprotective effects during IR [67,68], as well as vasodilator effects on the systemic and pulmonary circulation [69].…”
Section: Effect Of Prostaglandin E1mentioning
confidence: 99%
“…Similar to NO, PGE1 has cardioprotective effects during IR [67,68], as well as vasodilator effects on the systemic and pulmonary circulation [69]. Fang et al reported that pretreatment of human umbilical vein endothelial cells with PGE1 significantly protected those cells from H 2 O 2 -induced cell death [66]. And this effect might depend, at least in part, on the upregulation of NO expression [66].…”
Section: Effect Of Prostaglandin E1mentioning
confidence: 99%
See 1 more Smart Citation
“…Este medio está constituido por la formulación basal estándar recogida en publicaciones previas (132) De cada grupo de muestras (I y S) se realizaron 2 cultivos, uno basal, sin fármaco, y otro con alprostadil, a una concentración de 5ng/ml. La concentración se basó en estudios similares realizados en células endoteliales (133,134) El medio se cambió cada 12 horas. Por tanto, de cada paciente se obtuvieron 4 cultivos (grupo I basal, grupo I con alprostadil, grupo S basal, grupo S con alprostadil).…”
Section: Obtención De Las Muestras Y Cultivounclassified